Leveraging Digital Technologies for Informal Learning And Teacher Competency Development in Southern Pakistan - Majeed, Muhammad Kahsif; Ahmad, Tunku Badariah (Journal of Research, Innovation, and Strategies for Education (RISE), 2025)
This The rapid integration of digital technologies in education has transformed informal learning and teacher competency development, particularly in regions like Southern Pakistan, where access to resources is often limited. Leveraging digital platforms enhances English language acquisition and teachers’ functional skills, fostering 21st-century learning environments. Despite the growing use of Information and Communication Technologies (ICT) in education, limited research explores the combined impact of AI usage, digital competencies, and informal digital learning on teachers’ functional skills in Islamic schools in Southern Pakistan, particularly within informal learning contexts. This has important implications for improving instructional quality not only general education setting. This study aims to investigate the role of digital technologies in enhancing teachers’ functional competency, identify preferred digital platforms and activities for informal learning, and examine the influence of individual differences on engagement in informal digital learning among Islamic school teachers in Southern Pakistan. The findings may also inform the digital training need modernizing education delivery. Adopting a quantitative cross-sectional survey design, data were collected from 450 Islamic school teachers using purposive sampling based on established inclusion criteria. Data were analyzed using SPSS 22, with multiple linear regression assessing the influence of AI usage, digital competencies, and informal digital learning on teachers’ functional skills. Results revealed that informal digital learning had the strongest effect (β = 0.41, p < 0.001), followed by digital competencies (β = 0.35, p < 0.001) and AI usage (β = 0.28, p < 0.01), explaining 47% of the variance (R² = 0.47). AI’s smaller effect size suggests its underutilization in teaching practices. These findings highlight the need for enhanced teacher training in AI integration and digital competencies to maximize informal learning benefits, which can extend to professional development program in education as well, promoting competent Islamic teachers in Southern Pakistan.